用适当的方法解方程.
(1)x2-4x-3=0;
(2)(x-3)2+2x(x-3)=0;
(3)x2+5x-6=0;
(4)7x(5x+2)=6(5x+2);
(5)(3x-2)(3x-5)=-2;
(6)(x-3)2+(x-3)=0.
(1)x2-4x-3=0,
b2-4ac=(-4)2-4×1×(-3)=28,
x=4± 28 2
x1=2+
,x2=2-7
.7
(2)(x-3)2+2x(x-3)=0,
(x-3)(x-3+2x)=0,
x-3=0,x-3+2x=0,
x1=3,x2=1.
(3)x2+5x-6=0,
(x+6((x-1)=0,
x+6=0,x-1=0,
x1=-6,x2=1.
(4)7x(5x+2)=6(5x+2),
7x(5x+2)-6(5x+2)=0,
(5x+2)(7x-6)=0,
5x+2=0,7x-6=0,
x1=-
,x2=2 5
.6 7
(5)(3x-2)(3x-5)=-2,
9x2-21x+12=0,
(3x-4)(3x-3)=0,
3x-4=0,3x-3=0,
x1=
,x2=1.4 3
(6)(x-3)2+(x-3)=0,
(x-3)(x-3+1)=0,
x-3=0,x-3+1=0,
x1=3,x2=2.